Development of hybrid natural/synthetic fiber reinforced polymer composite of recurve bow riser for Malaysian junior athletes - Farah Ayuni, Fauzi (2018)
The utilisation of natural fiber and the waste product has become necessary in order to develop sustainability in various industries. The usage of natural fibers in the sport-oriented industries has increased in the recent years. As the recurve bow is the only type of bow that is used in the Olympic Games, it is crucial to design a recurve bow for the use of Malaysian junior archers. This study aims to analyse a recurve bow riser for the Malaysian junior athletes uses hybrid natural fiber as an alternative material. This study is divided into three phases: the set-up and preparation phase, experiment phase and analysis and validation phase. In the set-up and preparation phase, a mixture of natural fiber such as kenaf fiber and pineapple leaf fiber and epoxy was poured into the mold and left to dry at room temperature for 24 hours. The pineapple leaf fiber and kenaf fiber content were varied between 5 wt.% until 20 wt.%. This mixture was prepared using hand lay-up technique. Nine samples were cut according to ASTM D3039 and ASTM D790 for tensile and flexural testing respectively. The experiments of the tensile and flexural test were also conducted on the various compositions of hybrid materials in the experiment execution phase. The pineapple leaf fiber and kenaf fiber were varied between 5 wt.% and 10 wt.%, were respectively hybridised with 95 wt.% and 90 wt.% carbon fiber and glass fiber (95 CF/5 PALF, 95 CF/5 K, 90 CF/10 PALF, 90 CF/10 K , 95 GF/5 PALF, 95 GF/5 K, 90 GF/10 PALF and 90 GF/10 K) with the overall fiber content fixed to 40 wt.%. The best hybrid natural fiber composite material was selected after the mechanical properties assessment was conducted. In the analysis and validation phase, the static structural analysis of the riser was executed on the alternative design of the recurve bow riser. The analysis on the recurve riser has been conducted after the result of draw length was obtained. The finding from the pre-experiment suggests that both pineapple leaf fiber and kenaf fiber 5 wt.% and 10 wt.% could be used in the experiment phase. Results from the study showed that the material property of the best composition is 95 CF/5 PALF because it achieved the highest tensile strength, flexural strength and lower density. The composition was then used in the finite element analysis. In the finite element analysis, the maximum displacement of the alternative design of the recurve riser with 95 CF/5 PALF composite showed 98 % reduction in deformation compared to a previous established study. It can be concluded that the alternative design of the recurve riser is suitable for the alternative material. It can sustain the force applied by the Malaysian junior athletes when they aim at the target board at a full drawn bow position. In addition, the 95 CF/5 PALF composite meets the requirement of the mechanical properties, which is in the same range as aluminum alloy. Therefore, the hybrid composition can be used as a new alternative material to make a recurve riser. The developed recurve riser can be very beneficial for both athletes and coaches during training.